(untitled) (Al-Qamar, 2019)
Progeny is a serious issue in family matters. Indeed, posterity is a basic matter of course among human beings. The extraordinary development of medical science in the last few decades and paramount researches regarding artificial techniques to become a parent raise several questions among bioethicist and theologians. These techniques are not only related with science or medical field, but as a matter of fact, it involves many bioethical, religious and law related challenges. This article, therefore, seeks to explicate a very modern mean of treat infertility called surrogacy and surrogate mother according to Islamic jurisprudence in the light of contemporary theological arguments. Although the main point is to elaborate the status and position of surrogacy according to the Islamic perspective. Moreover, other relevant points regarding contemporary legislation in Muslim countries are also discussed. The article looks at the pertinent problems faced by the society regarding the application of such artificial techniques.